2014
DOI: 10.3389/fnbeh.2014.00199
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-prefrontal cortical circuitry in anxiety and depression phenotypes: pivotal role of pre- and post-synaptic 5-HT1A receptor expression

Abstract: Decreased serotonergic activity has been implicated in anxiety and major depression, and antidepressants directly or indirectly increase the long-term activity of the serotonin system. A key component of serotonin circuitry is the 5-HT1A autoreceptor, which functions as the major somatodendritic autoreceptor to negatively regulate the “gain” of the serotonin system. In addition, 5-HT1A heteroreceptors are abundantly expressed post-synaptically in the prefrontal cortex (PFC), amygdala, and hippocampus to mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 136 publications
4
157
0
2
Order By: Relevance
“…When comparing the effect of cholinergic and serotonergic modulation, the frontal and thalamic networks were more affected by the latter. This is consistent with observations in neurological disorders, such as depression and autism, characterized by frontal impairments and aberrant serotonergic functioning (Jeong et al 2009;Albert et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…When comparing the effect of cholinergic and serotonergic modulation, the frontal and thalamic networks were more affected by the latter. This is consistent with observations in neurological disorders, such as depression and autism, characterized by frontal impairments and aberrant serotonergic functioning (Jeong et al 2009;Albert et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…It is interesting that the prefrontal cortex and hippocampus were selected to measure neurosteriod biosynthesis in this study. Both the brain regions play an important role in emotional processing, fear conditioning and explicit memory that are relevant to anxiety and depression (Albert et al, 2014;Dias et al, 2012). Previous studies showed that prefrontal cortex and hippocampus contribute to memory formation in the fear associated network in addition to regulating subsequent expression of fear (Herry et al, 2010;Maren et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Both the brain regions are important in emotional processing, fear conditioning and explicit memory and play a role in anxiety and depression (Albert et al, 2014;Dias et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Chronic L-dopa specifically affected the caudal extent of the dorsal DRN and the PFC, two brain regions involved in affective behaviors (Lowry et al, 2005(Lowry et al, , 2008Warden et al, 2012;Albert et al, 2014). The crosstalk between these two regions is involved in fear and anxiety responses in rats (Hashimoto et al, 1999;Bishop et al, 2004;Amat et al, 2005;Forster et al, 2006) and several preclinical and clinical studies propose that chronic L-dopa therapy for Parkinson's disease could result in mood disturbances, such as anxiety and depression (Damasio et al, 1971;Choi et al, 2000;Borah and Mohanakumar, 2007;Eskow Jaunarajs et al, 2010.…”
Section: Discussionmentioning
confidence: 99%